Chromosomal dynamics in Senna: comparative PLOP–FISH analysis of tandem repeats and flow cytometric nuclear genome size estimations - Nguyen, Thi Hong; Kang, Byung Yong; Kim, Hyun Hee (Frontiers in Plant Science, 2023)
Introduction: Tandem repeats (TRs) occur abundantly in plant genomes. They play essential roles that affect genome organization and evolution by inducing or generating chromosomal rearrangements such as duplications, deletions, inversions, and translocations. These impact gene expression and chromosome structure and even contribute to the emergence of new species.We investigated the effects of TRs on speciation in Senna genus by performing a comparative analysis using fluorescence in situ hybridization (FISH) with S. tora-specific TR probes. We examined the chromosomal distribution of these TRs and compared the genome sizes of seven Senna species (estimated using flow cytometry) to better understand their evolutionary relationships.Results: Two (StoTR03_159 and StoTR04_55) of the nine studied TRs were not detected in any of the seven Senna species, whereas the remaining seven were found in all or some species with patterns that were similar to or contrasted with those of S. tora. Of these studies species, only S. angulata showed significant genome rearrangements and dysploid karyotypes resembling those of S. tora. The genome sizes varied among these species and did not positively correlate with chromosome number. Notably, S. angulata had the fewest chromosomes (2n = 22) but a relatively large genome size.Discussion: These findings reveal the dynamics of TRs and provide a cytogenetic depiction of chromosomal rearrangements during speciation in Senna. To further elucidate the dynamics of repeat sequences in Senna, future studies must include related species and extensive repeatomic studies, including those on transposable elements.